Relationship between Vascular Cell Adhesion Molecule-1 (Vcam-1) Level with Severity Degree of COVID-19 Patients at General Hospital H. Adam Malik Medan - Elvira; Siregar, Jelita; Lubis, Inke Nadia Diniyanti; Herman Hariman (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: The mechanism and pathogenesis of COVID-19 that distinguishes asymptomatic, mild, moderate, severe to critical symptoms is not yet known with certainty. Endothelial dysfunction and immune thrombosis serve as a profound pathogenic mechanism in COVID-19. Vascular Cell Adhesion Molecule-1 (VCAM-1) is a major regulator of leukocyte adhesion that contributes to the formation of thrombosis. The purpose of the study determine the relationship between VCAM-1 level with the severity degree in COVID-19 patients. Methods: An analytical study with a cross-sectional design was conducted from September – March 2022. This study was followed by 50 patients aged over 18 years with moderate, severe, and critical degrees of COVID-19 admitted to Haji Adam Malik General Hospital Medan by excluding malignancy and pregnancy patients. Serum VCAM-1 levels were measured using Chemwell Analyzer. Results: Among 50 patients, 33 patients (66%) were male and 17 patients (34%) were female. The mean age was 57 years with the youngest 19 years old and the oldest 81 years old. The median level of VCAM-1 was 23,02 ng/mL (10.96 ng/mL - 50.63 ng/mL). The median concentration of VCAM-1 was 37.85 ng/mL (15,59 – 50.63), 36.68 ng/mL (19.58 – 49.71), and 18.83 ng/mL (10.96 – 46.32) for critical, severe, and moderate degree respectively (p = 0.001). The cut-off value of VCAM-1 levels to predict the severity of COVID-19 is 32.01 ng/mL. Conclusions: There is a significant relationship between VCAM-1 levels and the severity of COVID-19.